Investigation of the relationship between BAT activity and thermal comfort under short-term cold temperature exposure - Tian Tian; Yi Shang; Jing Gao; Yuanfeng Lu; Rui Huang; Xuetao Hou (Scientific Reports)
Abstract Brown adipose tissue (BAT) plays a critical role in human thermogenesis and metabolic regulation. This study used infrared thermography to investigate the effects of short-term cold exposure on BAT activity and thermal sensation. Twelve healthy young adults were exposed to three ambient temperatures (17 °C, 19.5 °C, and 22.5 °C) for 120 min. Skin temperatures in the supraclavicular (SCV) and sternum (STR) regions were recorded every 10 min to estimate BAT activation, and subjective thermal sensation, comfort, and acceptability were assessed throughout exposure. Results showed that BAT activity, as indicated by the SCV–STR temperature difference (ΔT), increased most rapidly during the first 30 min of exposure and gradually plateaued by 120 min. Lower ambient temperatures induced faster BAT activation in the early phase; however, differences between conditions diminished over time and were no longer statistically significant by 120 min. Subjective thermal responses varied significantly across conditions. Environments perceived as ‘cold’ or ‘cool’ led to discomfort after 60–90 min, whereas the ‘slightly cool’ condition maintained thermal comfort and acceptability throughout. Despite slower initial BAT activation under this condition, cumulative ΔT at 120 min was comparable to colder environments. These findings suggest that using subjective thermal sensation as a reference may offer a more accurate and individualized approach to designing cold exposure environments. Prolonged exposure to a Slightly Cool environment (~ 120 min) may effectively activate BAT while preserving thermal comfort, providing potential benefits for metabolic health and indoor climate design.